2014
DOI: 10.1051/epjconf/20146800036
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Take-Out Food Packaging Attributes: Conjoint Analysis and Quality Function Deployment Approach

Abstract: Abstract. This research aims to investigate the importance of take-out food packaging attributes, using conjoint analysis and QFD approach among consumers of take-out food products in Jakarta, Indonesia. The conjoint results indicate that perception about packaging material (such as paper, plastic, and polystyrene foam) plays the most important role overall in consumer perception. The clustering results that there is strong segmentation in which take-out food packaging material consumer consider most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Designers must consider the basics of the packaging product functions in a sustainable food packaging design to draw up solutions after the issues have been identified. In general, the basic packaging functions are containment, protection and preservation, marketing and communications [38,39]. The hybrid approach proposed in this work to compute solutions in the conceptual design of NFBC food containers is therefore illustrated in Fig.…”
Section: Methodology Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Designers must consider the basics of the packaging product functions in a sustainable food packaging design to draw up solutions after the issues have been identified. In general, the basic packaging functions are containment, protection and preservation, marketing and communications [38,39]. The hybrid approach proposed in this work to compute solutions in the conceptual design of NFBC food containers is therefore illustrated in Fig.…”
Section: Methodology Of Studymentioning
confidence: 99%
“…The main aim of the relationship matrix is to build a relation between 'What' and 'Hows'. [39]. Then, Kano values ('k' values) will be obtained from Kano model analysis where Kano class decides the value of 'k'.…”
Section: Methodology Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Functions of food packaging are related to the physical proper-ties of the food in order to protect and preserve it, at the same time encouraging hygiene and safety [62]. Others also mentioned that food packaging also ensure food products transport-ed according to their made-to-order set-ups and amount suitable with the time they will be eaten; convenience and protected in dispensing products (easy-open features and re-closability); to add handiness to the food products; and also assist in sales increment [8], [62]. Packaging is also considered as one of the way in communicating messages to consumers and providing information and also instructions [62].…”
Section: Food Packaging: Materials Requirementmentioning
confidence: 99%
“…Others also mentioned that food packaging also ensure food products transport-ed according to their made-to-order set-ups and amount suitable with the time they will be eaten; convenience and protected in dispensing products (easy-open features and re-closability); to add handiness to the food products; and also assist in sales increment [8], [62]. Packaging is also considered as one of the way in communicating messages to consumers and providing information and also instructions [62]. A research by Widaningrum (2014) on the elements of designing a takeout food packaging in Indonesia by using combined Conjoint Analysis and Quality Function Deployment (QFD) technique found that the 'packaging material attributes' have the highest importance values [63].…”
Section: Food Packaging: Materials Requirementmentioning
confidence: 99%